"DITARIK" Literasi Cryptocurrency Oleh Asosiasi Kripto: Observasi Komunitas Di Platform X Terhadap Peningkatan Minat Masyarakat - Rhiswandi, Rhandi (Tractare: Jurnal Ekonomi-Manajemen, 2025)
The development of crypto assets in Indonesia shows a significant increasing trend, in line with the growing public interest in digital investment instruments. However, high interest is often not balanced by an adequate level of literacy, thus posing potential risks such as misinformation, financial losses, and excessive speculation. This study aims to analyze the role of crypto associations in encouraging cryptocurrency literacy through the community on platform X (Twitter), as well as its impact on increasing public interest. The research method used is non-participatory observation with a descriptive qualitative approach. Data was collected through monitoring the official accounts of crypto associations, uploaded educational content, and the interaction of the Indonesian crypto community on the X platform. The results of the study show that the literacy built by crypto associations through social media is able to increase public awareness and curiosity. Educational threads, literacy campaigns, and community discussions have been proven to encourage interest growth, as reflected in increased engagement, further information searches, and conversations about how to invest. However, the literacy spread by associations is often less popular than the narratives built by influencers or non- official communities. These findings underscore the importance of collaboration between crypto associations and the digital community in creating an inclusive, balanced, and sustainable literacy ecosystem to drive increased interest while reducing risks to society.